2017
DOI: 10.1002/rcm.7811
|View full text |Cite
|
Sign up to set email alerts
|

Selected ion flow tube study of the reactions of H3O+ and NO+ with a series of primary alcohols in the presence of water vapour in support of selected ion flow tube mass spectrometry

Abstract: This detailed study has provided the kinetics data, including the secondary hydrated ion product distributions, for the reactions of a number of volatile primary alcohols with the SIFT-MS reagent ions H O and NO , which allows their analyses by SIFT-MS in humid air and also helps in the interpretation of proton transfer reaction (PTR)-MS data. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 33 publications
(43 reference statements)
3
20
0
1
Order By: Relevance
“…At m/z 79.075, another association ion was observed to interfere with benzene. This peak was assigned to the [C 3 H 7 OH]H 3 O + ion, which is attributed to hydrated propanols 99 . These interferences have a big impact in the analysis of benzene in process gases like biogases and can obscure quantitative assessments, because such gases are typically rich in acetic acid, sulfur compounds, and propanols and additionally are saturated with water vapor, 1 which would favor the formation of association clusters.…”
Section: Resultsmentioning
confidence: 99%
“…At m/z 79.075, another association ion was observed to interfere with benzene. This peak was assigned to the [C 3 H 7 OH]H 3 O + ion, which is attributed to hydrated propanols 99 . These interferences have a big impact in the analysis of benzene in process gases like biogases and can obscure quantitative assessments, because such gases are typically rich in acetic acid, sulfur compounds, and propanols and additionally are saturated with water vapor, 1 which would favor the formation of association clusters.…”
Section: Resultsmentioning
confidence: 99%
“…As a CI‐based analytical technique, the relevant ion chemistry associated with the reaction of volatile compounds with the reagent ions is vital to the accurate identification and quantification of trace gases using SIFT‐MS. Several product ion distribution studies have been reported on CI using H 3 O + , NO + , and O 2 + precursor ions for a range of applications and for a wide variety of organic compounds including alcohols, aldehydes and ketones, carboxylic acids, esters, indoles, N‐ and O‐containing heterocyclic compounds, organosulfur and organoselenium, oxygenated biogenic/non‐methane volatile organic compounds, terpenes and terpenoids, siloxanes, and other compounds with biological applications …”
Section: Resultsmentioning
confidence: 99%
“…What we have learned so far is that the dominant ion‐molecule reaction process involved is ligand switching of analyte molecules, A, with H 2 O ligands in the reagent H 3 O + (H 2 O) n cluster ions. This is most likely if A is a polar molecule, as many SIFT experiments have shown, 35,36 when analyte ions AH + (H 2 O) n ‐1 result. The often‐assumed proton transfer from the reagent cluster ions to A molecules forming AH + ions will, in most cases, be endothermic, and can rarely occur.…”
Section: Discussionmentioning
confidence: 99%